2021
DOI: 10.1038/s41598-021-94032-8
|View full text |Cite
|
Sign up to set email alerts
|

Assisted peritoneal dialysis: a feasible KRT modality for frail older patients with end-stage kidney disease (ESKD)

Abstract: Assisted PD is used as an alternative option for the growing group of frail, older ESKD patients unable to perform their own PD. This study was undertaken to investigate the outcomes of assisted PD in older patients by comparing assisted PD patients with self-care PD patients. This study included all patients aged 70 and above who started on PD in our hospital from 2009 to 2018. Patients were followed up until death, PD cessation or to the end of the study (December 31, 2019). Risk factors associated with mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…In this situation, assisted PD by trained staff or family members has recently attracted a lot of attention. Several studies demonstrated that assisted PD presented equality or superiority in mortality and peritonitis risk compared with self-care PD [ 37 , 38 ]. Furthermore, assisted PD can be beneficial in risk of transfer to HD, especially to frail patients with low exercise capacity [ 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation, assisted PD by trained staff or family members has recently attracted a lot of attention. Several studies demonstrated that assisted PD presented equality or superiority in mortality and peritonitis risk compared with self-care PD [ 37 , 38 ]. Furthermore, assisted PD can be beneficial in risk of transfer to HD, especially to frail patients with low exercise capacity [ 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that assisted PD presented equality or superiority in mortality and peritonitis risk compared with self-care PD [ 37 , 38 ]. Furthermore, assisted PD can be beneficial in risk of transfer to HD, especially to frail patients with low exercise capacity [ 37 , 39 ]. The Frail and Elderly Patient Outcomes on Dialysis study demonstrated that the quality of life of elderly patients on assisted PD was similar to those of patients receiving in-center HD, and treatment satisfaction was higher on assisted PD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can offer helper-assisted CAPD with three different types of helpers: family members, domestic helpers, and nursing home staff (who are semiskilled health care assistants) [ 27 ]. Some other Chinese reports described the use of family-member or domestic worker paid by the employer, as helpers [ 28 ], selected according to education, with no health care background required, only able to read and write [ 29 ].…”
Section: Main Textmentioning
confidence: 99%
“…der peritonitisfreien Zeit. 55,6 % der Patienten verstarben im Beobachtungsintervall, 8,9 % wechselten zur HD und bei 30 % erfolgte die Therapie weiterhin mittels der PD 14 .…”
Section: Klinische Ergebnisse Zur Assistierten Pdunclassified